Measurements of light transfer through drift ice and landfast ice in the northern Baltic Sea - Elina Kari; Arttu Jutila; Anna Friedrichs; Matti Leppäranta; Susanne Kratzer (Oceanologia, 2020)
Summary: The aim of this study was to investigate the light transfer through sea ice with a focus on bio-optical substances both in fast ice and in the drift ice zones in the northern Baltic Sea. The measurements included snow and ice structure, spectral irradiance and photosynthetically active radiation below the sea ice. We also measured the concentrations of the three main bio-optical substances which are chlorophyll-a, suspended particulate matter, and coloured dissolved organic matter (CDOM). These bio-optical substances were determined for melted ice samples and for the underlying sea water. The present study provides the first spectral light transfer data set for drift ice in the Baltic Sea. We found high CDOM absorption values typical to the Baltic Sea waters also within sea ice. Our results showed that the transmittance through bare ice was lower for the coastal fast ice than for the drift ice sites. Bio-optical substances, in particular CDOM, modified the spectral distribution of light penetrating through the ice cover. Differences in crystal structure and the amount of gas inclusions in the ice caused variation in the light transfer. Snow cover on ice was found to be the dominant factor influencing the light field under ice, confirming previous studies. In conclusion, snow cover dominated the amount of light under the ice, but did not modify its spectral composition. CDOM in the ice absorbs strongly in the short wavelengths. As pure water absorbs most in the long wavelengths, the light transfer through ice was highest in the green (549–585 nm).